Optimization of Fixed Deposit Rules Using the Bisection Method - Azalia, Nur Azalia Binti A zarudin; Mahathir Mohamad (Enhanced Knowledge in Sciences and Technology, 2026)
The fixed deposit investment is generally considered as low-risk financial tools but it is difficult to establish the best parameters like interest rate or investment time because of the nonlinearity of compound interest. This paper suggests the use of the Bisection Method, a method of numerical root-finding, in order to optimise the fixed deposit investment parameters. A compound interest formula mathematical model was written and converted to a nonlinear equation to be solved numerically. Bisection Method was used with MATLAB and tested on five cases of simulation to either determine the interest rate required or the investment period to be used to obtain a given maturity value. The findings show that it exhibits a solid convergence of within a set tolerance limit, and high numerical accuracy and stability across all instances. These results show that the Bisection Method is a simple, stabilised and efficient technique of optimising fixed deposit, which demonstrates the existence of practicality of numerical techniques in financial planning and decision-making.